2022
DOI: 10.5902/1980509867600
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>seed priming</i> with NaCl on the induction of salinity tolerance in <i>Myracrodruon urundeuva</i> Allemão <i>in vitro</i>

Abstract: Soil salinization is an environmental factor that frequently occurs in semi-arid regions around the world and seed priming technique is one of the alternatives to obtain the greatest establishment of seedlings in the field, through the induction of tolerance to environmental stresses. This research aimed to evaluate the effect of seed priming with NaCl on the induction of salinity tolerance in Myracrodruon urundeuva Allemão in vitro. The research was carried out at the Center for Strategic Technologies of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It was demonstrated that rice seed priming by SA increases seed vitality [42]. Salts are frequently utilized for seed priming [43,44]. Pretreatment with mineral salts (halo-priming) is an easy, low-cost, and low-risk technique effective in seed priming for plantations under salinity stress conditions [45].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that rice seed priming by SA increases seed vitality [42]. Salts are frequently utilized for seed priming [43,44]. Pretreatment with mineral salts (halo-priming) is an easy, low-cost, and low-risk technique effective in seed priming for plantations under salinity stress conditions [45].…”
Section: Introductionmentioning
confidence: 99%